Cholesteryl Hemiazelate Present in Cardiovascular Disease Patients Causes Lysosome Dysfunction in Murine Fibroblasts - Lopes, Elizeth (2023)
Funding Information: This work was financially supported by the FCT (Foundation for Science and Technology of the Portuguese Ministry of Science and Higher Education), Refs. 2022.01305.PTDC and 2022.03249.PTDC. The Coimbra Chemistry Centre (CQC) is supported by the FCT through projects UIDB/00313/2020 and UIDP/00313/2020. E.L. is the holder of a PhD fellowship from the FCT (2021.06265.BD). A.R.A.M. was funded by the FCT Stimulus of Scientific Employment Individual Support Call 2017 (CEECIND/01006/2017). R.P. was funded by the NHLBI Division of Intramural Research (ZIA HL006151-10). Publisher Copyright: © 2023 by the authors.